The creation of 'a world after its own image': a genealogy of transparency - Adams, Rachel Margaret (Department of Private Law, 2017)
This thesis concerns the rise of transparency as a discursive fact of modern society. It seeks to understand both why and how the concept has come to be dominant within global neoliberal capitalism. From governments and political parties, to businesses and non-profit organisations, diverse institutions across the globe are embracing 'transparency'. Yet, despite its prominence, transparency remains vague and undefined, with scholarship largely devoted to expressing its merits and exploring ways to strengthen its practice. This has allowed transparency to gain its discursive power and, eventually, to become dominant. I turn to the work of Michel Foucault to problematise the transparency discourse with a view to unravel the effects of its discursive power. Through a Foucaultian critique, I come to read transparency as a depoliticising régime of truth ‒ one that is part and parcel of the Western will-to-power of neoliberalism, which excludes and, within this exclusion, contains, other realities. I identify transparency as an elusive and abstract metaphor, while defining it as a discursive practice of 'making visible'. My analysis follows the Foucaultian lines of archaeology, discourse, and governmentality, drawing these analytical strands together into a genealogy of transparency. The thesis notes the historical arrival of transparency within an ocularcentric episteme of the Western Enlightenment which privileges ideas of visibility ‒ an episteme from which neoliberalism also arises. I continue to trace the proselytisation of transparency upon the Global South, and its de-legitimisation of other forms of governance. The analysis then explores how transparency works within a dispositif (a relational field of power) of the current neoliberalist moment, creating a depoliticising illusion of a society that can be seen, known and understood. Further, I discuss how transparency is seeking to produce transparent subjects who are made visible to the disciplining powers of its discourse. In conclusion, my enquiry raises questions about an affinity between transparency and a hegemonic neo-colonial project to fashion a world in its own image: in the image of whiteness – a homogenous and de-politicised centre from which all else 'deviates'. Yet, I note a profound paradox at play. For transparency signals a marked absence, a paradoxical invisibility. Thus, as it seeks to create a world after its own image, it is in fact working towards its own inevitable unworking and absence.